Prechemotherapy Transperitoneal Robotic-Assisted Partial Nephrectomy (RAPN) for a Wilms Tumor: Surgical and Oncological Outcomes in a Four-Year-Old Patient - Marcello Della Corte; Elisa Cerchia; Marco Oderda; Paola Quarello; Franca Fagioli; Paolo Gontero; Simona Gerocarni Nappo (MDPI AG, 2023)
Background: Wilms tumor (WT) is the most frequent renal tumor in children. The SIOP-UMBRELLA Guidelines allow for nephron-sparing surgery (NSS) in syndromic patients, as well as in cases of small (<300 mL) non-syndromic unilateral WTs, without lymph node involvement, and with a substantial expected remnant renal function, following neoadjuvant chemotherapy. We present a case of prechemotherapy transperitoneal robot-assisted partial nephrectomy (RAPN) for a unilateral, non-syndromic Wilms tumor. Methods: A four-year-old child presented with a solid mass measuring 3.6 cm in diameter involving the upper right renal pole, incidentally detected during an abdominal echotomography. CT scan and abdominal MRI revealed no local infiltration or lymph node involvement, suggesting that the exophytic mass could be easily resected via an NSS robotic approach. Preoperative imaging did not strongly suggest WT. A virtual 3D reconstruction of the tumor was performed. Results: After the oncologic board approval, a robot-assisted partial nephrectomy with an intraperitoneal approach was performed. Histopathological analysis confirmed the diagnosis of WT. The patient subsequently received 10 doses of vincristine as adjuvant chemotherapy. A 28-month follow-up showed no tumor recurrence. Conclusions: Intraperitoneal RAPN may be an option for selected WT and warrants consideration as a challenging but advantageous approach.